Faktor Penentu Minat Muzakki Membayarkan Zakat Pada Lembaga Amil Zakat Dengan Kepercayaan Sebagai Variabel Mediasi - Mohammad Alfian; Hesti Widianti; Arifany Ferida (JPA : Journal of Public Accounting, 2021)
: Indonesia is the country with the largest Islamic religion in the world. Muslims have a duty to pay the zakat. As a country with the largest Islamic religion in the world, it indirectly has the potential for the management of zakat. Good zakat management can be used as a medium in reducing the distance between the able and underprivileged. Good zakat management can be done by amil zakat institutions. In fact, the distribution of zakat is still not optimal because there are still many muzakki who distribute zakat independently so it is not maximal. In this study conducted a test on the determining factors of interest muzakki pay zakat to institutions amil zakat with trust as a variable mediation. This study used PLS as its analysis method and used SmartPLS 3 as a statistical test tool. It was obtained that the zakat pick-up service negatively affects the interest of muzakki in paying zakat to the institution of ammil zakat and has no effect on the trust of muzakki so that the trust does not succeed in becoming a mediation variable. The acceptance service directly positively affects the interest of muzakki in paying zakat to the institution of amil zakat and affects the trust of muzakki, so that the trust manages to be a mediation variable from the influence of the admission service directly to the interest of muzakki in paying zakat.